The Permeability Changes in Clayey Soil - Fadzil, Faizhafizi; Norshah , Syamimi; Ngisa, Husnina; Mohd Razali, Siti Nooraiin (Multidisciplinary Applied Research and Innovation, 2022)
Based on the results of experimental studies on the factors influencing the value of the permeability coefficient. It is observed that several factors play an important role in the permeability that will affect the soil structure. Furthermore, all experimental data obtained are data that have been combined from experimental data of other researchers. There are several important factors that have been selected to show the level of influence of these factors which is able to affect the value of soil permeability. Among the important factors, these are the main factors that stand out in influencing the permeability coefficient of clay which are void ratio, porosity, maximum dry density and optimum moisture content Besides, for data selection method must go through several screening processes to indicate the eligibility of each of the data. Thus, a graph can be generated to show the relationship between the value of the permeability coefficient and the factors that influence it.